The ultimate depression survival guide : protect your savings, boost your income, and grow wealthy even in the worst of times - Weiss, Martin D. (John Wiley & Sons, 2009)
Offers advice to limit real estate and stock losses, build and protect nest eggs, and recognize when the sinking economy finally hits bottom